Creating a Positive PLA Experience: A Step-by-Step Look at University PLA - Leiste, Sara M.; Jensen, Kathryn (International Review of Research in Open and Distributed Learning, 2011)
A prior learning assessment (PLA) can be an intimidating process for adult learners. Capella University’s PLA team has developed best practices, resources, and tools to foster a positive experience and to remove barriers in PLA and uses three criteria to determine how to best administer the assessment. First, a PLA must be motivating, as described by the ARCS model. Second, it must enable success. Finally, it must use available resources efficiently. The tools and resources developed according to these criteria fall into two categories: staff and online resources. PLA programs can use both to ensure that all departments provide consistent communication to learners about the PLA process, which will foster a positive experience. The PLA online lab houses centralized resources and offers one-on-one interaction with a facilitator to assist learners step-by-step in the development of their petitions. Each unit contains resources, examples, and optional assignments that help learners to develop specific aspects of the petition. By following the examples and recommendations, learners are able to submit polished petitions after they complete the units. The lab facilitator supports learners throughout the units by answering questions and providing recommendations. When learners submit their petitions, the facilitator reviews it entirely and provides feedback to strengthen the final submission that goes to a faculty reviewer. All of these individuals and tools work together to help create a positive experience for learners who submit a PLA petition. This article shares these resources with the goal of strengthening PLA as a field.